2013
DOI: 10.1177/0363546513498989
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of the Anterior Cruciate Ligament Femoral Footprint Using 3 Different Approaches in Single-Bundle Reconstruction

Abstract: To improve the coverage of the native femoral footprint with a single-bundle graft, in addition to the entry point it may also be necessary to consider the orientation of the drilling to increase the dimensions of the area while respecting the anatomic constraints of the femoral bone and graft geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…33,34 A number of researchers have suggested that anteromedial approaches or outside-in approaches (or both) can yield tunnels in more anatomic positions than transtibial approaches. [35][36][37][38][39][40][41][42] In an anatomic study of ACL attachment locations using 20 human cadaveric knees, Zantop et al 25 reported that the center of the femoral AM bundle was located along the Blumensaat line at a distance of 18.5% of the sagittal diameter of the femur and at 22.3% of the height measured perpendicular to the Blumensaat line. However, other studies reported these respective parameters with considerable variability, as follows: 26.4% and 25.3% in a radiographic study of 7 cadaveric specimens, 30 21% and 24% in an anatomic study of 22 cadaveric knees with intact ACLs, 43 21.7% and 33.2% in a 3D CT study of 8 cadaveric knees, 31 and 27.7% and 16.3% in a study of 71 patients who underwent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 A number of researchers have suggested that anteromedial approaches or outside-in approaches (or both) can yield tunnels in more anatomic positions than transtibial approaches. [35][36][37][38][39][40][41][42] In an anatomic study of ACL attachment locations using 20 human cadaveric knees, Zantop et al 25 reported that the center of the femoral AM bundle was located along the Blumensaat line at a distance of 18.5% of the sagittal diameter of the femur and at 22.3% of the height measured perpendicular to the Blumensaat line. However, other studies reported these respective parameters with considerable variability, as follows: 26.4% and 25.3% in a radiographic study of 7 cadaveric specimens, 30 21% and 24% in an anatomic study of 22 cadaveric knees with intact ACLs, 43 21.7% and 33.2% in a 3D CT study of 8 cadaveric knees, 31 and 27.7% and 16.3% in a study of 71 patients who underwent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the position of the femoral tunnel in patients who underwent conventional transtibial and anatomic ACL reconstruction15,2123). The transtibial technique appears to cause a graft that is oriented anteriorly with limited ability to restore the oblique orientation of the ACL or normal knee stability2,9).…”
Section: Discussionmentioning
confidence: 99%
“…• Anatomic tunnel placement according to native femoral ACL footprint (compared to TT technique) [ 14 ].…”
Section: Advantagesmentioning
confidence: 99%